将Y=X+1代入余下的两式得:
2X+X+1+Z=1 3X+Z=0 (1)
X-2X-2+Z=-6 -X+Z=-6+2=-4 (2)
(1)减(2)得:3X+X=4 4X=4 X=1
将X=1代入3X+Z=0得:3+Z=0 Z=-3
将X=1代入Y=X+1得:Y=1+1=2
答:X=1;Y=2;Z=-3。
(2) 2x+2y+z=4 ①
2x+y+2z=7 ②
x+2y+2z=-6 ③
②-①:z-y=3 z=3+y
代入①、③:
2x+3y=1 ④
x+4y=-12 ⑤
④-2⑤:-5y=25 y=-5 x=-12-4y=8 z=-2
记得采纳哦~
(1)y=x+1 代入到(2)得(4);代入到(3)得(5)
(2)2x+y+z=1
(3)x-2y+z=-6
(4)2x+x+1+z=1---- 3x+z=0
(5)x-2(x+1)+z=-6---- -x+z=-4
(4)-(5)
4x=4
x=1
y=2
z=-3
(1)2x+2y+z=4两边同时×2得(4)
(2)2x+y+2z=7与(3)相减得(6)
(3)x+2y+2z=-6
(4)4x+4y+2z=8(与(3)相减得(5)
(5)3x+2y=14
(6)x-y=13---- x=13+y 代入到(5)
3(13+y)+2y=14
39+3y+2y=14
5y=-25
y=-5
x=8
z=4-2x-2y=4-16+10=-2